L-NAME-induced Preeclampsia: correction of functional disorders of the hemostasis system with Resveratrol and Nicorandil - Elena G. Stupakova; Galina A. Lazareva; Vladimir V. Gureev; Irina N. Dolzhikova; Lyudmila A. Zhilinkova; Anastasia V. Gureeva (Belgorod National Research University, 2019)
Introduction. Preeclampsia is a formidable disease of the second half of pregnancy, leading to severe complications, including disability and even death. Many authors have recognized the correlation between the severity of preeclampsia and the degree of disturbances in the hemostasis system. In this regard, the objective of this study was to assess inhibition of platelet aggregation and the possibility of its correction with resverаtrol and nicorandil. Materials and methods. The study was performed on 250 mature white Wistar female rats weighing 250-300 g. The platelet aggregation induced by ADP, collagen, ristomycin, adrenaline was determined, as well as PTT, TT, aPTT, fibrinogen, and the clotting time. Results and discussion. Introduction of resverаtrol and nicorandil resulted in a decrease in thrombocyte aggregation capacity from 53.8 ± 2.60% to 22.1 ± 1.25% and 37.1 ± 1.79%, respectively, when using ADP as an inducer. The clotting time was from 841 ± 42 s up to 1135 ± 33 s and 1034 ± 26 s, respectively. In addition, there was an increase in temporal parameters of plasma-coagulation hemostasis and a decrease in plasma fibrinogen content. The use of glibenclamide resulted in partial cancellation of the positive effects of resverаtrol and nicorandil, with an increase in platelet aggregation to 28.9 ± 1.8% and 43.9 ± 1.2% when using ADP as an inducer and a decrease in the thrombosis time to 988 ± 26 s and 950 ± 22 s, respectively. Conclusion. In animals with experimental preeclampsia, there were disturbances in the hemostasis system, comparable to those in the clinical situation. The use of resverаtrol and nicorandil leads to a pronounced correction of hemostasis parameters. The positive effects of the studied pharmacological agents are mediated by several mechanisms, including K+ATP channels.